Selected Short Stories - Jalal, Mir (''ADA University'', 2017)
"Mir Jalal Selected Short Stories" is a collection of Mir Jalal's best short stories and is one of the important works in Azerbaijani literature. This book presents stories that showcase his mastery in exploring human nature, social issues, and the complexities of Azerbaijani society. Among the stories included are "Dried Up Meetings", "Anket", "Anketov Mirza", "The Shade of the Willow Tree", "Foreign Illness", "Peachs", and "Matishga". Each story touches upon a unique theme, reflecting both personal and collective experiences, and vividly portraying Azerbaijani life. Jalal's stories provide readers with the opportunity to reflect on both individual life and social-cultural aspects. This book helps to better understand Mir Jalal's contributions to Azerbaijani literature and his position in the literary world.
Keywords: Azerbaijani literature -- 20th century.; Pashayev, Mir Jalal, 1908-1979 -- Works; Short stories, Azerbaijani; Fictional works -- Azerbaijani authors; Azerbaijan -- Literature and history